Peer victimization and sympathy development in childhood: The moderating role of emotion regulation. Issue 2 (24th September 2020) - Jambon, Marc; Colasante, Tyler; Ngo, Hazel; Dys, Sebastian; Malti, Tina
Abstract: Although peer victimization is widely considered to be detrimental to children's well‐being, knowing what it feels like to be harmed is also thought to contribute to children's sense of concern for others. However, research has yet to establish a clear link between peer victimization and sympathy during childhood. Across two samples of Canadian 4‐ and 8‐year‐olds (total N = 504), we examined whether children's emotion regulation capacities (ER) moderated the victimization–sympathy link. Study 1 ( n = 300; 33% European origin; 73% of caregivers held bachelor's degree or higher) examined the interactive effects of victimization and child‐ and caregiver‐reported ER on children's self‐reported sympathy assessed concurrently and 1 year later. Concurrently, victimization was positively associated with sympathy for children higher in self‐reported ER and for boys higher in caregiver‐reported ER. Longitudinally, victimization positively predicted changes in sympathy from 4 to 5 years of age for children higher in self‐reported ER. No longitudinal interaction effects emerged for caregiver‐reported ER or in older children. Using the same caregiver‐reported ER measure, Study 2 ( n = 204; 30% European origin; 65% of caregivers held bachelor's degree or higher) replicated this pattern in a different cross‐sectional sample of 4‐ and 8‐year‐olds. These results provide initial support for the hypothesis that victimization experiences may facilitate other‐oriented concern in children who can effectively regulate their emotions.